THE EFFECT OF SMALL GROUP DISCUSSION STRATEGY ON THE SECOND YEAR STUDENTS’ ABILITY IN COMPREHENDING HORTATORY EXPOSITION TEXTS AT MAN 1 TELUK KUANTAN - Mulya Putri Handayani; Fadly Azhar; Fakhri Ras (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research seeks to find out whether or not there is a significant effect of Small Group Discussion (SGD) strategy on the second year students’ ability in comprehending hortatory exposition texts at MAN 1 Teluk Kuantan. This research used the pre-experimental research design of one group pre-test post-test design. The selected sample was XI MIA 1 students which consisted of 35 students. The sample was selected by using cluster random sampling technique. The results showed that the mean score of post-test (76.00) was higher than mean score of pre-test (70.03). Therefore, Alternative Hypothesis (Ha) was accepted and Null Hypothesis (Ho) was rejected. It could be concluded that there was a significant effect of Small Group Discussion strategy on the second year students’ ability in comprehending hortatory exposition texts at MAN 1 Teluk Kuantan. In other words, teaching reading comprehension through SGD strategy is an effective way to solved the students’ problem on the reading comprehension.Key Words: Effect, Small Group Discussion strategy, Reading Ability